2007
DOI: 10.1007/s10750-006-0518-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies on phosphorus transference occuring between Microcystis aeruginosa and its attached bacterium (Pseudomonas sp.)

Abstract: Phosphorus release from Microcystis aeruginosa and attached bacterium (Pseudomonas sp.) isolated from Lake Taihu was examined using a phosphorus isotope tracer in order to investigate the phosphorus transference between the two species. Our results reveal that the amount of phosphorus released form 32 P-saturated M. aeruginosa is determined by its growth phase and most of phosphorus is assimilated by Pseudomonas finally while the amount of phosphorus released from 32 P-saturated Pseudomonas is also determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…Heterotrophic bacterial growth is enhanced by extracellular polysaccharide secretion from Microcystis aeruginosa (Shen et al ., ). Phosphorus cycling between the colonial cyanobacterium, M. aeruginosa , and attached bacteria, such as Pseudomonas , was reported (Jiang et al ., ). These preceding observations suggest a close relationship between Microcystis and the associated bacteria.…”
Section: Introductionsupporting
confidence: 62%
“…Heterotrophic bacterial growth is enhanced by extracellular polysaccharide secretion from Microcystis aeruginosa (Shen et al ., ). Phosphorus cycling between the colonial cyanobacterium, M. aeruginosa , and attached bacteria, such as Pseudomonas , was reported (Jiang et al ., ). These preceding observations suggest a close relationship between Microcystis and the associated bacteria.…”
Section: Introductionsupporting
confidence: 62%
“…Microcystis species grow into large mucilaginous aggregates, which comprise a microscale mucus region called the phycosphere, and this region is generally colonized by associated bacteria 19 . Fluctuations in the bacterial diversity associated with Microcystis- blooms are often observed in many environmental samples 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In another recent study using dialysis bags, we observed that P is transferred from Pseudomonas to M. aeruginosa when M. aeruginosa is in growth phase, while P transfer from M. aeruginosa to Pseudomonas occurs when M. aeruginosa is in decline phase (Jiang et al 2007). Although these results are both sensitive and highly repeatable, it is difficult to extrapolate these results to explain the field observation in which Microcystis spp.…”
Section: Introductionmentioning
confidence: 72%
“…The green fluorescence protein (gfp)-labeled attached bacterium Pseudomonas was acquired by transforming a plasmid (pJZ383, containing the gfp gene) into Pseudomonas, which was isolated from the mucilage of Microcystis in Lake Taihu, China (Jiang et al 2007). We chose the gfp-labeled clones and tested their growth stability by comparing the biomass with unlabeled clones in parallel cultures every 12 h for 3 days, then selected the optimal clone.…”
Section: Organisms and Their Cultivationmentioning
confidence: 99%
See 1 more Smart Citation